Adolescente: Compreendendo sua susceptibilidade às lesões intraepiteliais cervicais - Danno, Camila Hidemi; Takeda, Elisabete; Mazzetto, Fernanda Moerbeck Cardoso [UNESP]; Tonhom, Sílvia Franco da Rocha (My University, 2016)
Objective: This is a literature review that seeks to understand the cervical intraepithelial lesions in adolescents. Data source: 20 articles inventoried by the Latin American and Caribbean Health Sciences (LILACS). Data synthesis: Adolescence is the age group that is more susceptible to contact with HPV as well as injuries caused by its infection, including Cervix Cancer. The lack of knowledge of this population is the main cause of various consequences in the sphere of this disease. Conclusion: The health professional must have an extended and thorough look at the sexual health of adolescents, and when associated with intersectional actions, can contribute to the development of guidelines focused on comprehensive care, seeking sexual prevention and adolescent's sexual health promotion.
Adolescent: Understanding their susceptibility to intraepithelial cervical injuries
Keywords: Adolescent; Cervical intraepithelial neoplasia; Papillomavirus infections; Vaginal smears